2014
DOI: 10.1371/journal.pone.0085927
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factor Profiles for Peripheral Artery Disease and Carotid Atherosclerosis among Chinese Older People: A Population-Based Study

Abstract: ObjectivesEpidemiological data concerning atherosclerotic disease among older people in rural China are sparse. We seek to determine prevalence and cardiovascular risk factor profiles for peripheral artery disease (PAD) and carotid atherosclerosis (CAS) among Chinese older people living in a rural community.MethodsThis cross-sectional study included 1499 participants (age ≥60 years, 59.0% women) of the Confucius Hometown Aging Project in Shandong, China. From June 2010–July 2011, data were collected through in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Moreover, there was significant positive correlation between Bollinger score and each of total cholesterol and triglycerides in both study groups. The same results were observe in a study conducted by Liang et al (12) Limitations: Limitations of our study were: Relatively small sample size, inability to perform laboratory tests for the recent biomarker for PAD eg Markers of endothelial dysfunction; soluble cell adhesion molecules and Modulators of angiogenesis: soluble Tie 2, VEGF; hepatocyte growth factor. CONCLUSION We concluded that peripheral arterial disease differs among diabetic patients than non-diabetic patients in the following: Severity; being more severe in diabetics, Distribution; tends to more distal affection among diabetic patients, associated risk factors and predictors of severity; as in diabetics it depends more on HbA1C, GFR, dyslipidemia, hs-CRP and albuminuria while in non-diabetic patients it depends only on hs-CRP and dyslipidemia.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, there was significant positive correlation between Bollinger score and each of total cholesterol and triglycerides in both study groups. The same results were observe in a study conducted by Liang et al (12) Limitations: Limitations of our study were: Relatively small sample size, inability to perform laboratory tests for the recent biomarker for PAD eg Markers of endothelial dysfunction; soluble cell adhesion molecules and Modulators of angiogenesis: soluble Tie 2, VEGF; hepatocyte growth factor. CONCLUSION We concluded that peripheral arterial disease differs among diabetic patients than non-diabetic patients in the following: Severity; being more severe in diabetics, Distribution; tends to more distal affection among diabetic patients, associated risk factors and predictors of severity; as in diabetics it depends more on HbA1C, GFR, dyslipidemia, hs-CRP and albuminuria while in non-diabetic patients it depends only on hs-CRP and dyslipidemia.…”
Section: Discussionsupporting
confidence: 78%
“…To compare our results with previous studies, we searched PubMed to identify population‐based studies that reported the prevalence of CA detected by ultrasound in China, and summarized findings are shown in Table 4. Of these previous studies,16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26 only the CKB (China Kadoorie Biobank) study included a large sample of participants (N=24 822) from multiple geographic regions in China16; all other studies were geographically local. The CKB study reported that the overall prevalence of carotid plaque was 31%, which was much higher than the prevalence of 13.9% in the present study; however, the CKB study included participants with stroke (5.4%) or coronary heart disease (7.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies that excluded people with prior CVDs, the prevalence of carotid plaque was 9.7% in villages in Xinjiang,17 18.8% in Shanghai city,18 16.8% to 30.6% in Nanjing city,19 and 41.5% in a low‐income rural community in Tianjin 20. The reported overall prevalence of CA or increased IMT was from 11.2% in a rural community in Shandong21 to as high as 40.3% in Shenyang city 22. Different approaches in participant sampling and selection, ultrasound techniques, and diagnosis criteria may cause such substantial differences in the reported prevalence of CA and carotid plaque, although it is generally impossible to be certain based on published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple risk factors for atherosclerosis have been identified, including hyperlipoproteinemia, hypertension, diabetes, obesity, and smoking [29]. Clinical studies on children with homocystinuria have indicated a role of HHcy in the premature development of atherosclerosis and thromboembolism [30].…”
Section: Discussionmentioning
confidence: 99%